The introductory evaluation of possibility of using waste perlite powder in building polymer composites - Łukowski, Paweł; Sokołowska, Joanna; Kępniak, Maja (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper deals with possibility of use of waste perlite powder as a microfiller in the building polymer composites. The perlite powder influences the technological properties of the polymer mixes, while the mechanical properties of the hardened composite are not significantly affected. The obtained results confirm the possibility of rational use of the waste material, which is in agreement with the rules of the sustainable development in construction. Till now, 5 % (by mass) of conventional microfiller in the polyester composite have been successfully substituted by perlite powder, which means the utilization of large amounts of this waste, due to its low bulk density (< 100 kg/m3). The authors will attempt to increase the degree of substitution. However, it will require resolving some technological problems involved particularly with the deterioration of the polymer mixes workability by the addition of the perlite powder.